Status of macro and micro nutrients from deposited tailings in reclamation area, PT Freeport Indonesia, Timika - S Taberima; R Sarwom (Brawijaya University, 2016)
The reclamation program of deposited tailings (SIRSAT) is the obligation of the mining concession holder PT Freeport Indonesia (PTFI). The monitoring of soil and plant qualities regularly is part of the study of the success or performance of mining reclamation. The objective of research in the reclamation area was to study the uptake of macro and micronutrients in inactive tailings, andrepresentative plants that grow up on it. The result showed that pH was alkaline in the land of MP21 with its plants of M. sagoand C.nucifera, MP27 with Matoa (P.pinnata), both of the representative locations with tailings/soil depth of 0-20 cm and 20-40 cm, except the surface layer of MP21 has lower pH, i.e. neutral. The organic matter tends to be higher at MP21 with M. sago, followed by C. nucifera, while at MP27 with P. pinnata was very low on the surface layer (topsoil) and the bottom layer. MP27 was reclaimed in 2003 with P. pinnata, however these plants tend to be abnormal after being planted more than 10 years. While MP21 with M. sago and C. nucifera was more fertile due to high content of organic matter. Besides that, the tailings deposition at MP21 had became inactive tailings for longer, and were used for the land reclamation activities since 1992/1993. The uptake of macronutrients, especially K was high, which was found in both productive and old leaves in the representative plants of inactive tailings and natural soil. While the old leaves of P. pinnata produced the highest content of S, i.e. > 0,1%. Mnwas the highest in both of old leaves of C. nucifera (379,50ppm) and M. Sago(558 ppm) which were planted in the natural soil. These concentration levels were higher than normal criteria (> 300 ppm Mn). The uptake of Zn includes normal criteria, except in the productive leaves (170,67ppm), and also the old leaves (160.33 ppm), or exceeds of the normal criteria (> 100 ppm Zn) found in P. pinnata MP21.